Continuous watermelon cropping impairs plant growth by modifying soil biochemistry and rhizosphere microbial communities - Lv, HuiFang; Sang, Rui; Huang, LingLing; Long, YueChen; Xu, DeCong; Wang, MingXia; Zhang, QiAn; Jia, Li; Ding, QiangQiang; Yan, CongSheng; Zhang, HuanXin (Frontiers in Microbiology, 2025)
Continuous watermelon cropping leads to increases in soil-borne diseases, which negatively affect plant growth. We investigated the impact of continuous watermelon cropping on soil biochemical properties, enzyme activities, microbial biomass, occurrence of Fusarium wilt, diversity and structure of bacterial and fungal communities, as well as the relationship among these factors with plant growth. The results showed significant decreases in soil pH, OM, AN, AP, and AK contents (p < 0.05), while UA, APA, and DA were reduced, along with declines in MBC and MBN in the rhizosphere soil of continuous watermelon cropping (p < 0.05). The population of FON and Fusarium wilt incidence increased significantly after continuous cropping (p < 0.05). High-throughput sequencing analysis revealed that the richness and diversity of soil bacterial and fungal communities significantly decreased (p < 0.05). There were significant differences in bacterial and fungal community composition between the continuous cropping and control groups. Besides, the Pearson correlation analysis of plant growth and environmental factors revealed that soil parameters, including pH, SOM, AN, AP, UA, APA, DA, MBC, and the richness and diversity of bacterial and fungal communities all had significant effects on plant growth. Additionally, the incidence of Fusarium wilt and the population of FON negatively affected growth. In conclusion, we hypothesize that soil acidification, deterioration of biochemical properties, an increase in Fusarium wilt, and changes in microbial community structure are causes of poor watermelon growth.